2014
DOI: 10.1111/ijlh.12246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iron deficiency on hemoglobin A2% in obligate β‐thalassemia heterozygotes

Abstract: Iron deficiency was prevalent among north Indian βTT individuals, especially women. After adjusting for other causes of low HbA2 in βTT, iron deficiency, even when very severe, was very unlikely to interfere significantly with HbA2-based identification of βTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…These results show that, while HbA 2 tended to be lower in iron deficiency, it was not less than the cut‐off value of 3.5% used for detecting β‐thalassemia carriers. These observations were confirmed by a recent study with a larger cohort of patients in India . Neither study was focused on protracted and severe iron deficiency, and this will require further investigation.…”
Section: Iron Deficiency and Hba2 Levelssupporting
confidence: 56%
“…These results show that, while HbA 2 tended to be lower in iron deficiency, it was not less than the cut‐off value of 3.5% used for detecting β‐thalassemia carriers. These observations were confirmed by a recent study with a larger cohort of patients in India . Neither study was focused on protracted and severe iron deficiency, and this will require further investigation.…”
Section: Iron Deficiency and Hba2 Levelssupporting
confidence: 56%
“…Contradictory reports are available in literature showing variable findings of hemoglobin A 2 in individuals with iron deficiency anemia concomitant with β thalassemia trait. A study, conducted in India, reported that iron deficiency concomitant with β thalassemia trait was very unlikely to significantly affect the levels of hemoglobin A 2 in severe iron deficient females with concomitant β thalassemia trait 17. A study by Usman et al has shown that individuals with β thalassemia trait coexistent with iron deficiency anemia had normal hemoglobin A 2 levels that were confirmed by molecular analysis 18.…”
Section: Discussionmentioning
confidence: 96%
“…Study done in India among 752 samples found that 3.1% of them had borderline HbA2 values defined between 3.1-3.9% [10].…”
Section: Discussionmentioning
confidence: 96%